The legal status of a whistleblower following Law 2/2023 on the protection of whistleblowers and the fight against corruption - Sáez Lara, Carmen (LABOS Revista de Derecho del Trabajo y Protección Social, 2023)
The study of the conditions of access to the statute of protection, established by Law 2/2023, is addressed in this work, highlighting that the legal framework coexists with the framework of protection, designed by the jurisprudential doctrine, under the protection of the rights of freedom of information and expression, for persons who warn about infractions or irregularities with relevance to the public interest. Consequently, the relationship between the legal and judicial standard of protection of the informant, in case of public disclosure directly to the press, is examined. Finally, the deficit of the legal regulation is highlighted, both in relation to the accreditation of the status of whistleblower and in the specification of the protection measures that make up the aforementioned protective statute.
Keywords: Whistleblowers; legal protection; judicial protection; freedom of expression; truthful information